(untitled) (Community Based Medical Journal, 2026)
Negative autopsy, where postmortem examination fails to determine the cause of death, remains a significant challenge in forensic pathology. In Bangladesh, limited data exist on its frequency and contributing factors, hindering improvements in death investigation protocols. Understanding the prevalence and characteristics of negative autopsies is crucial for enhancing diagnostic accuracy in resource-constrained settings. A retrospective, cross-sectional study was conducted in the Department of Forensic Medicine & Toxicology, Sir Salimullah Medical College, Dhaka, Bangladesh, from January 2023 to December 2024. From 700 consecutive autopsies performed during this period, we purposively selected 130 cases (18.6%) meeting criteria for negative autopsy (inconclusive findings after complete gross, histopathological, and toxicological examinations). Data extraction included demographic characteristics, circumstantial evidence, and diagnostic test results. Among 130 cases, negative autopsies accounted for 18.5%, predominantly in males (62.3%) and adults aged 31–45 years (42.3%). Sudden unexplained death (45.4%) and suspected poisoning (32.3%) were leading circumstances. Significant associations emerged with delayed autopsy (more than 48 hours; 40.0%, p=0.012), incomplete history (45.4%, p=0.021), and lack of ancillary tests (67.7%, p=0.003). Seasonal peaks occurred in monsoon (48.5%, p=0.008). Our study reveals an 18.5% prevalence of negative autopsy, which is strongly linked to procedural delays and diagnostic limitations. Urgent implementation of 24-hour services, standardized protocols, and expanded testing capacity is needed to improve forensic accuracy in resource-constrained settings. CBMJ 2026 January: vol. 15 no. 01 P:138-143